In vitro antibacterial activity of crude medicinal plant extracts against ampicillin+penicillin-resistant Staphylococcus aureus - Samsudin, Nik Iskandar Putra; Lee, Hai Yen; Chern, P.E.; Ng, C.T.; Panneerselvam, L.; Phang, S.Y.; Tan, W.T.; Mahyudin, Nor Ainy (Universiti Putra Malaysia, 2018)
Staphylococcus aureus is the leading cause for foodborne diseases. Extensive use of antibiotics has led to emergence of antibiotic-resistant S. aureus. Hence, interest on natural plant-based alternative which limits the use of synthetic chemicals is growing. The present work evaluated the antibacterial capacity of garlic, aloe vera, galangal, pineapple peel, neem, papaya leaf, lemongrass, peppermint, nutmeg and clove separately extracted with hexane, ethanol and water to a final concentration of 10% w/v against ampicillin+penicillin-resistant isolates of S. aureus in vitro. Streptomycin was used as a drug control against the resistant isolates; BRS023, BRS068 and DRS072. According to the interpretive standards for inhibition zone diameter provided by the Clinical and Laboratory Standards Institute, isolates BRS068 and DRS072 were considered resistant (≤ 12 mm), and isolate BRS023 was considered intermediate (13-14 mm). Against these isolates, all crude plant extracts exhibited varying degrees of inhibition. However, a coherent trend was observed in the inhibition between resistant and intermediate isolates regardless of plants and solvents used. It was also found that extraction solvent types impacted the resulting antibacterial activity. In terms of positive inhibition, the solvents were ranked in the order of hexane (77%) > water (73%) > ethanol (57%). 10% hexane extract of galangal gave the overall highest inhibition zones (17.8 ± 1.4 mm) closely followed by 10% ethanol extract of nutmeg (16.3 ± 1.1 mm). Further phytochemical analyses of the antibacterial compounds from galangal and nutmeg, and their minimum inhibitory concentration (MIC) are needed. Potential applications of plant-based antibacterial compounds as natural, costeffective and less-toxic food preservatives against drug-resistant foodborne pathogens should be explored.